Cardiovascular risk factors are highly overrepresented in Swedish patients with psoriatic arthritis compared with the general population. (3rd May 2020) - Landgren, AJ; Bilberg, A; Eliasson, B; Larsson, I; Dehlin, M; Jacobsson, LTH; Klingberg, E
Abstract : Objectives : We aimed to determine the prevalence of cardiovascular risk factors in patients with psoriatic arthritis (PsA) followed at a large Swedish Rheumatology Clinic, and to compare differences in cardiovascular risk factors between men and women with PsA and with the general population. Method : A questionnaire was sent to patients with PsA registered at the Rheumatology Clinic at Sahlgrenska University Hospital, Gothenburg (n = 982). Comparisons with the general population were made using data from the Swedish National Public Health Survey. Descriptive statistics are presented. Body mass index (BMI) was calculated using self-reported height and weight. Results : Overall, 692 (70.6%) of the patients with PsA responded. The mean ± sd age was 55.6 ± 11.4 years and 52% were women. Obesity (BMI ≥ 30 kg/m 2 ) was more prevalent (p < 0.001) in patients with PsA (28.6%) than in matched subjects from the general population (16.3%). Hypertension was also more prevalent (p < 0.001) in PsA (40.3%) than in matched subjects from the general population (24.1%), as was diabetes, with a prevalence of 10.5% in the PsA population compared with 6.2% in matched subjects (p < 0.001). Conclusion : We found obesity to be highly overrepresented in patients with PsA compared with matched subjects from the general population. This difference was particularly seen in women with PsA. Hypertension and ever smoking were also more prevalent in women with PsA compared with matched subjects from the general population.